A glass fiber reinforced copolymerized flame-retardant nylon toughened composite material and a preparation method thereof
Patent Information
- Application Number
- CN202610916572.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-24
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]尽管上述专利中制备的尼龙复合材料具有较好的耐低温性能,但是对制备的材料的阻燃性能未进行进一步的研究
[0030] This invention modifies long-chain nylon with PA66 through copolymerization, and further modifies the copolymerized flame-retardant nylon 66 via blending and amide exchange reaction, significantly reducing the low-temperature glass transition temperature of the material and effectively improving the problems of molecular chain freezing and hydrogen bond hardening of nylon at low temperatures. The maleic anhydride groups in the graft compatibilizer can undergo a grafting reaction with the terminal amino groups of the nylon matrix to generate amyl acid or imide bonds. The silane coupling agent undergoes a hydrolytic condensation reaction with the surface of alkali-free glass fiber, constructing a bilayer structure of "chemical anchoring point - flexible interface layer" on the glass fiber surface. The graft compatibilizer can also undergo a similar anhydride-amino reaction with the residual amino groups already anchored on the glass fiber surface, chemically attaching elastomer segments to the glass fiber surface. Finally, the glass fiber surface is coated with a layer of elastomer with extremely low Tg, forming an "elastomer bridging" interface structure. Meanwhile, the flexible hydrophobic layer formed by long-chain alkylsilanes does not participate in the chemical reaction, but significantly reduces the surface energy of the glass fiber, promotes the uniform spreading of the elastomer, and allows for moderate fiber slippage and pull-out during low-temperature impact, further absorbing energy. The above multi-level reactions ultimately construct a three-dimensional covalent network with flexible anchoring on the glass fiber surface, intramolecular toughening of the nylon matrix, and uniform dispersion of chemically grafted elastomers. This enables the composite material to maintain excellent impact toughness even in extreme cold environments of -40°C, overcoming the technical bottleneck of traditional nylon which can only withstand -20°C to -30°C before becoming brittle. The addition of antioxidants effectively inhibits the oxidative degradation of nylon in cold environments. The synergistic effect of multiple substances in this invention buffers low-temperature thermal stress, reduces the initiation and propagation of microcracks, and significantly improves fatigue resistance and weather resistance, meeting the requirements for use in cold regions.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure QLYQS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of nylon material preparation technology, and in particular to a glass fiber reinforced copolymer flame-retardant nylon toughened composite material and its preparation method. Background Technology
[0002] Nylon is a type of polymer material whose main molecular chain contains repeating amide groups. It has high mechanical strength, excellent toughness, outstanding tensile and compressive strength and fatigue resistance, while also possessing good heat resistance, corrosion resistance, electrical insulation, wear resistance and a high softening point. Nylon has low melt viscosity, good flowability, fast filling speed, short molding cycle and excellent processing performance. It is currently the most widely used of the five major engineering plastics and has been widely used in many industrial fields such as automotive, rail transportation, electronics and electrical, aerospace and textiles.
[0003] In existing technologies, the low-temperature impact performance of nylon is often improved through methods such as glass fiber reinforcement and elastomer blending for toughening. However, conventional modified systems have limited low-temperature resistance limits, typically only meeting the usage requirements of -20°C to -30°C. When the temperature drops further to below -40°C, the material's toughness deteriorates significantly, leading to problems such as brittleness and failure. In recent years, with economic development and continuous innovation in materials science, the low-temperature environment in northern regions has placed more stringent demands on nylon materials for some key structural components. These materials must maintain high toughness, impact resistance, and fatigue resistance in extreme cold environments down to -40°C, while also meeting flame-retardant safety standards.
[0004] The prior art CN119735950A discloses an ultra-low temperature toughened nylon glass fiber reinforced composite material, which comprises 50-70 parts of nylon resin, 20-40 parts of glass fiber, 5-10 parts of toughening agent, 0.1-5 parts of crosslinking agent, and 0.1-10 parts of other additives; the toughening agent includes maleic anhydride modified elastomer; the crosslinking agent includes aminated cage-type silsesquioxane; the composite material has a notched impact strength of ≥15 kJ / m in a simply supported beam at 50℃. 2 The impact bar does not break at least once in a 50°C impact test. CN110437611A discloses a reinforced, toughened, and ultra-low temperature resistant nylon composite material, comprising: 55-75 parts of nylon resin, 15-30 parts of glass fiber, 5-12 parts of toughening agent, and 0.5-2 parts of lubricant; the toughening agent is a mixture of amino-terminated polydimethylsiloxane, epoxy-terminated polydimethylsiloxane, and organosilicon elastomer toughening agent; the glass fiber is glass fiber modified with an amino- or epoxy-containing silane coupling agent.
[0005] Although the nylon composite materials prepared in the aforementioned patents have good low-temperature resistance, the flame retardant properties of the prepared materials have not been further studied.
[0006] Traditional flame-retardant nylons often achieve their flame-retardant function through physical blending with added flame retardants. However, the flame retardants have poor compatibility with the nylon matrix, leading to uneven dispersion and weak interfacial bonding. This not only further weakens the material's low-temperature toughness but also accelerates aging and mechanical property degradation in low-temperature environments, making it difficult to simultaneously achieve flame retardancy, low-temperature toughness, and resistance to extreme cold aging. Currently, copolymer flame-retardant PA66 materials that combine excellent low-temperature impact resistance, flame retardancy, and fatigue resistance, and can withstand extreme cold environments down to -40°C, are still relatively scarce.
[0007] Therefore, developing a copolymer flame-retardant PA66 toughened composite material that can maintain high toughness, excellent flame retardancy, and resistance to aging and cracking at extreme low temperatures is of great engineering value and practical significance for meeting the application needs of structural components in cold working conditions in high-altitude and cold regions. Summary of the Invention
[0008] To address the problems existing in the prior art, this invention provides a glass fiber reinforced copolymer flame-retardant nylon toughened composite material and its preparation method. The synergistic effect of multiple substances in this invention buffers low-temperature thermal stress, reduces the initiation and propagation of microcracks, and significantly improves fatigue resistance and weather resistance, meeting the application requirements in cold regions.
[0009] To solve the above-mentioned technical problems, the present invention provides the following technical solution:
[0010] On one hand, the present invention provides a glass fiber reinforced copolymer flame-retardant nylon toughened composite material, which is composed of the following components in parts by weight: 25-35 parts copolymer long carbon chain nylon elastomer, 65-70 parts copolymer flame-retardant PA66, 20-30 parts alkali-free glass fiber, 2-5 parts graft compatibilizer, 0.3-0.8 parts compound antioxidant, 0.2-0.6 parts lubricant, 1.5-2 parts coupling agent, and 0.05-0.1 parts catalyst;
[0011] The copolymerized long-chain nylon elastomer is one of the copolymers of PA612, PA610, PA1313 and PA66; preferably, the long-chain nylon has a number-average molecular weight Mn of 15000~25000 g / mol and a molecular weight distribution index PDI of 1.5~2.5.
[0012] The alkali-free glass fiber has a diameter of 8-15 μm and a length of 2-6 mm.
[0013] Preferably, the preparation method of the copolymerized flame retardant PA66 can be found in CN113278200A, which involves the polymerization reaction of nylon 66 salt with a halogen-free phosphorus-based flame retardant. The structural formula of the halogen-free phosphorus-based flame retardant is as follows:
[0014] .
[0015] Furthermore, the copolymerized long-chain carbon nylon elastomer is prepared by the following method:
[0016] PA66 salt solution and long-chain nylon with a mass ratio of 30:70 were added to a high-temperature and high-pressure reactor. After sealing the reactor, the air inside was fully replaced with nitrogen, and then nitrogen was introduced to 0.1 MPa to maintain a slight positive pressure. The system was then heated to a prepolymerization temperature of 210 °C at a heating rate of 2 °C / min and kept at a constant pressure of 1.6 MPa for 1 h. After that, the pressure was slowly released while the temperature was gradually increased to 240 °C. The entire depressurization process lasted for 3 h. After the depressurization was completed, the reaction continued for 10 min under normal pressure. Finally, a vacuum was slowly drawn to promote the polycondensation reaction in the forward direction, and the temperature was kept constant at 245 °C for 20 min until the material reached the desired consistency. The material was then discharged, cooled, pelletized, and dried to obtain the copolymerized long-chain nylon elastomer.
[0017] Preferably, the graft compatibilizer is one of maleic anhydride-grafted polyolefin elastomer (POE-g-MAH), maleic anhydride-grafted ethylene-vinyl acetate elastomer (EVA-g-MAH), and maleic anhydride-grafted polypropylene elastomer (PP-g-MAH).
[0018] The coupling agent is γ-aminopropyltriethoxysilane and dodecyltrimethoxysilane in a mass ratio of 1:3.
[0019] Preferably, the compound antioxidant is composed of hindered phenolic antioxidant Irganox 1098 and phosphite antioxidant Irgafos 168, with a weight ratio of 1:1 to 1:1.5.
[0020] The lubricant is a stearate or a wax;
[0021] The catalyst is sodium hypophosphite.
[0022] On the other hand, the present invention also provides a method for preparing the above-mentioned glass fiber reinforced copolymer flame-retardant nylon toughened composite material, comprising:
[0023] (1) Preparation of copolymerized flame-retardant PA66;
[0024] (2) Preparation of copolymerized long-chain carbon nylon elastomers;
[0025] (3) Add the copolymer flame retardant PA66, copolymer long carbon chain nylon elastomer, graft compatibilizer, catalyst, compound antioxidant and lubricant to a high-speed mixer, set the speed to 800~1000 r / min, mix at room temperature for 5~10 min until all components are fully mixed and uniform.
[0026] (4) Start the twin-screw extruder and set the temperature according to the section: 240℃~290℃, die temperature 280℃~285℃, main machine speed 180~240rpm, control the torque at 55%~65%, and feed alkali-free glass fiber and coupling agent into the four sides when 1 / 3 of the screw remains to achieve uniform dispersion of each component.
[0027] (5) The material that was mixed evenly in step (3) is fed into the twin-screw extruder at a constant speed through an automatic feeder, and the material is melted and mixed in the barrel;
[0028] (6) The molten material is extruded into a continuous strip through the die head, introduced into a multi-stage water cooling tank for cooling, and after the surface moisture is dried, it is cut into uniform particles of 2-3 mm by a pelletizer. Then, post-treatment is performed to obtain glass fiber reinforced copolymer flame retardant nylon toughened composite material. The post-treatment is as follows: the particles are boiled in water at 90-105 ℃ for 2.5-3.5 h, and after boiling, they are soaked in water at 20-30 ℃ for 3-5 h.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] This invention modifies long-chain nylon with PA66 through copolymerization, and further modifies the copolymerized flame-retardant nylon 66 via blending and amide exchange reaction, significantly reducing the low-temperature glass transition temperature of the material and effectively improving the problems of molecular chain freezing and hydrogen bond hardening of nylon at low temperatures. The maleic anhydride groups in the graft compatibilizer can undergo a grafting reaction with the terminal amino groups of the nylon matrix to generate amyl acid or imide bonds. The silane coupling agent undergoes a hydrolytic condensation reaction with the surface of alkali-free glass fiber, constructing a bilayer structure of "chemical anchoring point - flexible interface layer" on the glass fiber surface. The graft compatibilizer can also undergo a similar anhydride-amino reaction with the residual amino groups already anchored on the glass fiber surface, chemically attaching elastomer segments to the glass fiber surface. Finally, the glass fiber surface is coated with a layer of elastomer with extremely low Tg, forming an "elastomer bridging" interface structure. Meanwhile, the flexible hydrophobic layer formed by long-chain alkylsilanes does not participate in the chemical reaction, but significantly reduces the surface energy of the glass fiber, promotes the uniform spreading of the elastomer, and allows for moderate fiber slippage and pull-out during low-temperature impact, further absorbing energy. The above multi-level reactions ultimately construct a three-dimensional covalent network with flexible anchoring on the glass fiber surface, intramolecular toughening of the nylon matrix, and uniform dispersion of chemically grafted elastomers. This enables the composite material to maintain excellent impact toughness even in extreme cold environments of -40°C, overcoming the technical bottleneck of traditional nylon which can only withstand -20°C to -30°C before becoming brittle. The addition of antioxidants effectively inhibits the oxidative degradation of nylon in cold environments. The synergistic effect of multiple substances in this invention buffers low-temperature thermal stress, reduces the initiation and propagation of microcracks, and significantly improves fatigue resistance and weather resistance, meeting the requirements for use in cold regions.
[0031] Simultaneously, it employs halogen-free phosphorus-based flame retardants and integrates flame-retardant units into the nylon molecular backbone through melt copolymerization to form an intrinsic flame-retardant structure. This avoids the defects of traditional physical blending flame retardants, such as uneven dispersion, easy precipitation, and easy migration. While achieving UL94 V-0 flame retardancy, it does not significantly degrade low-temperature toughness and mechanical strength. During combustion, it produces low smoke, low toxicity, and no corrosive gases, making it environmentally friendly and safe. It can be widely used in fields with stringent requirements for low-temperature toughness, flame retardancy, and safety, such as high-altitude rail transportation, low-temperature automotive components, outdoor electronic appliances, and special engineering structural components.
[0032] This invention employs a two-step process of copolymerization and melt blending, with controllable process parameters, a simple flow, and no need for special equipment. It can be scaled up using existing nylon polymerization and twin-screw extrusion equipment. At the same time, the system has good fluidity, short injection molding cycle, and excellent appearance and dimensional stability of the products. Moreover, the material is a copolymer-compatible system with stable component bonding. It is not prone to phase separation and additive precipitation during recycling and reprocessing. After multiple cycles, it retains high mechanical, toughness, and flame retardant properties. It is green and recyclable, and has outstanding industrial value. Detailed Implementation
[0033] To make the technical problems, technical solutions and advantages of the present invention clearer, a detailed description will be given below in conjunction with specific embodiments.
[0034] Unless otherwise specified, all materials and devices used in this invention are commercially available. The alkali-free glass fiber has a diameter of 8-15 μm and a length of 2-6 mm.
[0035] The copolymer flame retardant PA66 was prepared according to Example 1 of CN113278200A.
[0036] This invention provides a glass fiber reinforced copolymer flame-retardant nylon toughened composite material and its preparation method, with specific embodiments as follows.
[0037] Example 1
[0038] A glass fiber reinforced copolymer flame-retardant nylon toughened composite material is composed of the following components in parts by weight: 67.5 parts of copolymer flame-retardant PA66, 30 parts of PA610-co-PA66 copolymer, 3 parts of graft compatibilizer POE-g-MAH, 25 parts of alkali-free glass fiber, 0.5 parts of compound antioxidant (1010:168=1:1), 0.4 parts of zinc stearate, 1.8 parts of silane coupling agent (γ-aminopropyltriethoxysilane and dodecyltrimethoxysilane in a mass ratio of 1:3), and 0.08 parts of sodium hypophosphite.
[0039] The preparation method of the above-mentioned glass fiber reinforced copolymer flame-retardant nylon toughened composite material includes:
[0040] S1: Preparation of copolymer flame retardant PA66;
[0041] S2: Preparation of copolymerized long-chain carbon nylon elastomer: PA610 and PA66 salts with a mass ratio of 30:70 were weighed and dissolved in an equal mass (sum of the masses of PA610 and PA66) of deionized water. The mixture was stirred in a 70°C water bath for at least 30 minutes until fully dissolved. The solution was then transferred to a high-temperature, high-pressure reactor. After sealing the reactor, the air inside was completely replaced with nitrogen, and then nitrogen was introduced to maintain a slight positive pressure of 0.1 MPa. The system was then heated to a prepolymerization temperature of 210 °C at a heating rate of 2 °C / min and maintained at a constant pressure of 1.6 MPa for 1 hour. Afterward, the pressure was slowly released while the temperature was gradually increased to 240 °C, a process that lasted for 3 hours. After depressurization, the reaction continued for 10 minutes under normal pressure. Finally, a vacuum was slowly applied to drive the polycondensation reaction forward, and the temperature was maintained at 245 °C for 20 minutes. When the material reaches the desired consistency, it is discharged, cooled, pelletized, and dried to obtain the copolymerized long carbon chain nylon elastomer PA610-co-PA66.
[0042] S3: High-speed blending of the mixture: Add the copolymer flame retardant PA66, copolymer long carbon chain nylon elastomer, graft compatibilizer, catalyst, compound antioxidant, and lubricant to the high-speed mixer, set the speed to 900 r / min, and mix at room temperature for 10 min until all components are fully and evenly mixed.
[0043] S4: Melt blending and in-situ grafting toughening: Start the twin-screw extruder and set the temperature according to the section: 270℃, die temperature 285℃, main engine speed 180rpm, torque 60%. When 1 / 3 of the screw is left, side feed in alkali-free glass fiber and coupling agent to achieve uniform dispersion of each component. The uniformly mixed material is fed into the twin-screw extruder at a uniform speed through an automatic feeder. The material melts and blends in the barrel. Under the weak shearing action of the screw, a controllable amide exchange reaction occurs between the carbon chain nylon to form a random copolymer structure, achieving uniform dispersion of the toughening phase. This significantly improves low-temperature toughness without losing rigidity and prevents brittle fracture failure at low temperatures.
[0044] S5: Water-cooled shaping and pelletizing: The molten material is extruded into a continuous strip through the die head, introduced into a multi-stage water-cooling tank for cooling, and after the surface moisture is dried, it is cut into uniform particles of 2~3 mm by a pelletizer to obtain glass fiber reinforced copolymer flame retardant nylon toughened composite material.
[0045] Example 2
[0046] The only difference between this embodiment and Embodiment 1 is that PA610 in step S2 is replaced with PA612 of equal mass.
[0047] Example 3
[0048] The only difference between this embodiment and embodiment 1 is that PA610 in step S2 is replaced with an equal mass of PA1313, the amount of copolymerized long carbon chain nylon elastomer is 25 parts, and the amount of copolymerized flame retardant PA66 is 70 parts.
[0049] Example 4
[0050] The only difference between this embodiment and Embodiment 3 is that the amount of copolymerized long-chain nylon elastomer is 30 parts, and the amount of copolymerized flame-retardant PA66 is 67.5 parts.
[0051] Example 5
[0052] The only difference between this embodiment and Embodiment 4 is that the amount of copolymerized long-chain nylon elastomer is 35 parts, and the amount of copolymerized flame-retardant PA66 is 65 parts.
[0053] Example 6
[0054] A glass fiber reinforced copolymer flame-retardant nylon toughened composite material is composed of the following components in parts by weight: 70 parts of copolymer flame-retardant PA66, 30 parts of PA610-co-PA66 copolymer, 5 parts of graft compatibilizer PP-g-MAH, 30 parts of alkali-free glass fiber, 0.8 parts of compound antioxidant (1010:168=1:1), 0.2 parts of zinc stearate, 1.5 parts of silane coupling agent (γ-aminopropyltriethoxysilane and dodecyltrimethoxysilane in a mass ratio of 1:3), and 0.1 parts of sodium hypophosphite.
[0055] The preparation method of the above glass fiber reinforced copolymer flame retardant nylon toughened composite material is the same as in Example 1.
[0056] Example 7
[0057] A glass fiber reinforced copolymer flame-retardant nylon toughened composite material is composed of the following components in parts by weight: 68 parts of copolymer flame-retardant PA66, 28 parts of PA610-co-PA66 copolymer, 2 parts of graft compatibilizer EVA-g-MAH, 20 parts of alkali-free glass fiber, 0.3 parts of compound antioxidant (1010:168=1:1), 0.6 parts of zinc stearate, 2 parts of silane coupling agent (γ-aminopropyltriethoxysilane and dodecyltrimethoxysilane in a mass ratio of 1:3), and 0.05 parts of sodium hypophosphite.
[0058] The preparation method of the above glass fiber reinforced copolymer flame retardant nylon toughened composite material is the same as in Example 1.
[0059] To further illustrate the beneficial effects of the present invention, the following comparative examples were constructed.
[0060] Comparative Example 1
[0061] In this comparative example, the copolymerized long carbon chain nylon elastomer is omitted; the other conditions are the same as in Example 1.
[0062] Comparative Example 2
[0063] In this comparative example, the copolymer flame retardant PA66 was replaced with an equal mass of PA66, and the other conditions were the same as in Example 1.
[0064] Comparative Example 3
[0065] In this comparative example, the PA610-co-PA66 copolymer was replaced with an equal mass of PA610, and the other conditions were the same as in Example 1.
[0066] Comparative Example 4
[0067] In this comparative example, the copolymerized long-chain nylon elastomer was omitted, and the amount of copolymerized flame-retardant PA66 was 100 parts, POE-g-MAH was 10 parts, and the other conditions were the same as in Example 1.
[0068] Comparative Example 5
[0069] In this comparative example, the grafting compatibilizer was omitted, and the other conditions were the same as in Example 1.
[0070] Comparative Example 6
[0071] In this comparative example, the coupling agent is γ-aminopropyltriethoxysilane, and the other conditions are the same as in Example 1.
[0072] Comparative Example 7
[0073] In this comparative example, the coupling agent is dodecyltrimethoxysilane, and the other conditions are the same as in Example 1.
[0074] Comparative Example 8
[0075] In this comparative example, the coupling agents were γ-aminopropyltriethoxysilane and dodecyltrimethoxysilane in a mass ratio of 3:1, and the other conditions were the same as in Example 1.
[0076] Comparative Example 9
[0077] In this comparative example, the coupling agents were γ-aminopropyltriethoxysilane and dodecyltrimethoxysilane in a mass ratio of 1:1, and the other conditions were the same as in Example 1.
[0078] Comparative Example 10
[0079] In this comparative example, the coupling agents were γ-aminopropyltriethoxysilane and dodecyltrimethoxysilane in a mass ratio of 1:5, and the other conditions were the same as in Example 1.
[0080] Comparative Example 11
[0081] In this comparative example, the amount of PA610-co-PA66 copolymer used was 10 parts, and the other conditions were the same as in Example 1.
[0082] Comparative Example 12
[0083] In this comparative example, the amount of copolymer flame retardant PA66 used was 50 parts, and the other conditions were the same as in Example 1.
[0084] The composite materials prepared in Examples 1-7 and Comparative Examples 1-12 were subjected to performance testing. The tensile properties of the materials were tested according to GB / T1040.2–2025 "Determination of tensile properties of plastics—Part 2: Test conditions for molded and extruded plastics". The impact properties of the materials were tested according to GB / T1043.2–2018 "Determination of impact properties of simply supported beams of plastics—Part 2: Instrumented impact testing". The combustion properties of the materials were tested according to GB / T2406.2–2009 "Determination of combustion behavior of plastics by oxygen index method". The samples were ignited in an oxygen-nitrogen mixed atmosphere. The minimum oxygen content required to maintain combustion was determined by adjusting the oxygen concentration, and the average value of multiple test results was taken as the limiting oxygen index (LOI) of the material.
[0085] All samples were prepared to standard dimensions and conditioned for 24 hours at (23±2)℃ and (50±5)% relative humidity before testing. The average value of each test result was taken from no less than 5 parallel samples. The test results are shown in Table 1-2.
[0086] Table 1
[0087]
[0088] As shown in Table 1 above, the test results demonstrate that this invention uses alkali-free glass fiber and long-chain carbon nylon elastomer to reinforce and toughen copolymerized flame-retardant PA66. Maleic anhydride-polyolefin elastomer is used as a graft compatibilizer, and a low-shear melt blending method is employed to achieve a more uniform distribution of the elastomer within the flame-retardant PA66 molecular chain, thereby significantly improving the material's low-temperature toughness. The composite material prepared by this invention exhibits significantly improved impact strength at ultra-low temperatures (-40℃) with almost no impact on the material's inherent flame-retardant properties.
[0089] Table 2
[0090]
[0091] Table 2 shows that omitting the copolymerized long-chain nylon elastomer (Comparative Example 1), replacing the copolymerized long-chain nylon elastomer with ordinary long-chain nylon (Comparative Example 3), or omitting the copolymerized long-chain nylon elastomer and changing the amount of other substances (Comparative Example 4) significantly reduced the mechanical properties of the prepared composite material. Replacing the copolymerized flame-retardant PA66 with an equal mass of PA66 (Comparative Example 2) drastically reduced the flame-retardant properties of the prepared composite material, and its mechanical properties also decreased.
[0092] Omitting the graft compatibilizer (Comparative Example 5) or changing the type or amount of coupling agent (Comparative Examples 6-10), or changing the amount of PA610-co-PA66 copolymer (Comparative Example 11) or copolymer flame-retardant PA66 (Comparative Example 12), the low-temperature performance of the prepared composite material is significantly reduced.
[0093] In summary, this invention, through the synergistic effect of copolymerized long-chain carbon nylon elastomer, copolymerized flame-retardant nylon 66, graft compatibilizer, silane coupling agent, and alkali-free glass fiber, enables the composite material to maintain excellent impact toughness in extreme cold environments of -40 ℃, thus meeting the application requirements in cold regions.
[0094] The above description is a preferred embodiment of the present invention. For those skilled in the art, any improvements and modifications made without departing from the principles of the present invention should also be considered within the scope of protection of the present invention.
Claims
1. A glass fiber reinforced copolymer flame-retardant nylon toughened composite material, characterized in that, It is composed of the following components by weight: 25-35 parts copolymer long-chain carbon nylon elastomer, 65-70 parts copolymer flame retardant PA66, 20-30 parts alkali-free glass fiber, 2-5 parts graft compatibilizer, 0.3-0.8 parts compound antioxidant, 0.2-0.6 parts lubricant, 1.5-2 parts coupling agent, and 0.05-0.1 parts catalyst; The copolymerized long-chain nylon elastomer is a copolymer of long-chain nylon and PA66; the long-chain nylon is PA612, PA610 or PA1313.
2. The glass fiber reinforced copolymer flame-retardant nylon toughened composite material according to claim 1, characterized in that, The long-chain nylon has a number-average molecular weight (Mn) of 15,000 to 25,000 g / mol and a molecular weight distribution index (PDI) of 1.5 to 2.
5.
3. The glass fiber reinforced copolymer flame-retardant nylon toughened composite material according to claim 1, characterized in that, The copolymer flame retardant PA66 is obtained by the polymerization reaction of nylon 66 salt and halogen-free phosphorus flame retardant.
4. The glass fiber reinforced copolymer flame-retardant nylon toughened composite material according to claim 3, characterized in that, The structural formula of the halogen-free phosphorus-based flame retardant is as follows: 。 5. The glass fiber reinforced copolymer flame-retardant nylon toughened composite material according to claim 1, characterized in that, The copolymerized long-chain carbon nylon elastomer was prepared by the following method: PA66 salt solution and long-chain nylon were added to a high-temperature and high-pressure reactor. After sealing the reactor, the air inside was fully replaced with nitrogen, and then nitrogen was introduced to 0.1 MPa. The system was then heated to 210 °C at a heating rate of 2 °C / min and kept at a constant pressure of 1.6 MPa for 1 h. After that, the pressure was slowly released while the temperature was gradually increased to 240 °C. The entire depressurization process lasted for 3 h. After the pressure was released, the reaction continued for 10 min under normal pressure. Finally, a vacuum was slowly drawn and the temperature was kept constant at 245 °C. After reacting for 20 min, the material was discharged, cooled, pelletized, and dried to obtain copolymerized long-chain nylon elastomer.
6. The glass fiber reinforced copolymer flame-retardant nylon toughened composite material according to claim 1, characterized in that, The graft compatibilizer is one of maleic anhydride grafted polyolefin elastomer (POE-g-MAH), maleic anhydride grafted ethylene-vinyl acetate elastomer (EVA-g-MAH), and maleic anhydride grafted polypropylene elastomer (PP-g-MAH). The coupling agent is γ-aminopropyltriethoxysilane and dodecyltrimethoxysilane in a mass ratio of 1:
3.
7. The glass fiber reinforced copolymer flame-retardant nylon toughened composite material according to claim 1, characterized in that, The compound antioxidant is composed of hindered phenolic antioxidant Irganox 1098 and phosphite antioxidant Irgafos 168 in a mass ratio of 1:1 to 1:1.
5. The lubricant is a stearate or a wax; The catalyst is sodium hypophosphite; The alkali-free glass fiber has a diameter of 8-15 μm and a length of 2-6 mm.
8. The method for preparing the glass fiber reinforced copolymer flame-retardant nylon toughened composite material according to any one of claims 1-7, characterized in that, include: (1) Preparation of copolymerized flame-retardant PA66; (2) Preparation of copolymerized long-chain carbon nylon elastomers; (3) Add the copolymer flame retardant PA66, copolymer long carbon chain nylon elastomer, graft compatibilizer, catalyst, compound antioxidant and lubricant to a high-speed mixer, set the speed to 800~1000 r / min, mix at room temperature for 5~10 min until all components are fully mixed and uniform. (4) Start the twin-screw extruder and set the temperature according to the section: 240℃~290℃, die temperature 280℃~285℃, main machine speed 180~240rpm, control the torque at 55%~65%, and feed alkali-free glass fiber and coupling agent into the four sides when 1 / 3 of the screw remains to achieve uniform dispersion of each component. (5) The material that was mixed evenly in step (3) is fed into the twin-screw extruder at a constant speed through an automatic feeder, and the material is melted and mixed in the barrel; (6) The molten material is extruded into a continuous strip through the die head, introduced into a multi-stage water cooling tank for cooling, and after the surface moisture is dried, it is cut into uniform particles of 2~3 mm by a pelletizer. Then, post-processing is carried out to obtain glass fiber reinforced copolymer flame retardant nylon toughened composite material.
9. The preparation method according to claim 8, characterized in that, The post-processing in step (6) is as follows: the particles are boiled in water at 90~105℃ for 2.5~3.5 hours to adjust the humidity. After boiling, they are soaked in water at 20~30℃ for 3~5 hours.
Citation Information
Patent Citations
Reinforced and toughened ultra-low temperature resistant nylon composite material and preparation method and application thereof
CN110437611A
Phosphorus-containing flame retardant as well as preparation method and application thereof
CN113278200A
Ultra-low temperature toughened nylon glass fiber reinforced composite material and preparation method and application thereof
CN119735950A